1989
DOI: 10.1056/nejm198904273201703
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Time of Administration of Calcium Acetate on Phosphorus Binding

Abstract: Phosphorus binders are given to patients with renal failure to increase gastrointestinal excretion of phosphorus. To determine the relative importance of the binding of dietary as compared with endogenous phosphorus and to determine the optimal dose schedule, we gave either 4.4 g of calcium acetate (25 mmol of calcium) or a placebo to six normal subjects on each of seven different schedules in a randomized sequence. The net gastrointestinal balance of phosphorus and calcium was determined by a one-day lavage t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(61 citation statements)
references
References 10 publications
2
58
0
1
Order By: Relevance
“…As with all phosphate binders, calcium-based binders are most effective when taken with meals (which also limits calcium absorption). 10 They should be prescribed in conjunction with moderate dietary phosphate restriction, ideally supervised by an accredited practising dietitian. Phosphate-rich foods with a high phosphate to protein ratio (processed foods, fast foods and cola drinks) are best avoided, while foods with a high biologic value (e.g.…”
Section: Phosphate Bindersmentioning
confidence: 99%
“…As with all phosphate binders, calcium-based binders are most effective when taken with meals (which also limits calcium absorption). 10 They should be prescribed in conjunction with moderate dietary phosphate restriction, ideally supervised by an accredited practising dietitian. Phosphate-rich foods with a high phosphate to protein ratio (processed foods, fast foods and cola drinks) are best avoided, while foods with a high biologic value (e.g.…”
Section: Phosphate Bindersmentioning
confidence: 99%
“…Moreover, the temporal relationship with meals is crucial to bind dietary phosphate adequately. It is well established that unsynchronized administration of binders significantly increases the proportion of dietary phosphorus absorbed compared with concomitant administration of binder with meals (24,35,36,46,87).…”
Section: Prescription Errormentioning
confidence: 99%
“…So, many efforts have been aimed to design low phosphate diets and to evaluate new phosphate-binding agents, tailoring their administration in relation to the dietary phosphate intake [8]. Previous studies demonstrated that 70% of the absorbed dietary phosphate is actively transported in duodenum and jejunum by an Na-dependent co-transport mechanism; the other 30% is passively absorbed in the same intestinal segments by diffusion [9].…”
Section: Introductionmentioning
confidence: 99%